A comparative whole genome analysis of Helicobacter pylori from a human dense South Asian setting. Issue 1 (18th October 2020) - Qumar, Shamsul; Nguyen, Trang Hoa; Nahar, Shamsun; Sarker, Nishat; Baker, Stephen; Bulach, Dieter; Ahmed, Niyaz; Rahman, Motiur
Abstract: Helicobacter pylori, a Gram‐negative bacterium, is associated with a wide range of gastric diseases such as gastritis, duodenal ulcer, and gastric cancer. The prevalence of H pylori and risk of disease vary in different parts of the world based on the prevailing bacterial lineage. Here, we present a contextual and comparative genomics analysis of 20 clinical isolates of H pylori from patients in Bangladesh. Despite a uniform host ethnicity (Bengali), isolates were classified as being part of the HpAsia2 (50%) or HpEurope (50%) population. Out of twenty isolates, eighteen isolates were cagA positive, with two HpEurope isolates being cagA negative, three EPIYA motif patterns (AB, AB‐C, and ABC‐C) were observed among the cagA ‐positive isolates. Three vacA genotypes were observed with the s1m1i1dic1 genotype observed in 75% of isolates; the s1m2i1d1c2 and s2m2i2d2c2 genotypes were found to be 15% and 10% of isolates, respectively. The non‐virulent genotypes s2m2i2d2c2 was only observed in HpEurope population isolates. Genotypic analysis of oipA gene, present in all isolates, revealed five different patterns of the CT repeat; all HpAsia2 isolates were in "ON" while 20% of HpEurope isolates were genotypically "OFF." The three blood group antigen binding adhesins encoded genes ( bab genes) examined and we observed that the most common genotype was ( babA / babB /‐) found in eight isolates, notably six were HpAsia2 isolates. The babA gene was found in all HpAsia2 isolates but present in only half of the HpEurope isolates. In silico antibiotic susceptibility analysis revealed that 40% of the strains were multi‐drug resistant. Mutations associated with resistance to metronidazole, fluoroquinolone, and clarithromycin were detected 90%, 45%, and 5%, respectively, in H pylori strain. In conclusion, it is evident that two populations of H pylori with similar antibiotic profiles are predominant in Bangladesh, and it appears that genotypically the HpAisa2 isolates are potentially more virulent than the HpEurope isolates.